Psychometric properties of commonly used morningness-eveningness questionnaires in adults and adolescents by applying structural equation modeling - Panjeh, Sareh [UNIFESP] (2023)
Introduction:morningness-eveningness refers to individual differences in sleep-wake patterns, preferred time for activities and levels of alertness in the morning and evening. It is believed to be a unidimensional construct but this has not been properly tested via robust structural equation modeling techniques. Objective: to investigate the underlying factor structure of two morningness-eveningness questionnaires that are frequently used in the international literature in adults (the MorningnessEveningness Questionnaire: MEQ) and in children and adolescents (the MorningnessEveningness Scale for Children: MESC). Methods: the MEQ’s internal consistency was investigated by conducting exploratory factor analysis in four different adult samples, two each from Brazil and the United Kingdom (total N = 3,457). Confirmatory factor analysis was applied to the MESC based on a sample of Brazilian adolescents (N=394) to investigate if the factor solution found in the MEQ could also be used to structure the confirmatory model. Results: we found a three-correlated factor solution with acceptable model fit indexes across all four studied adult populations who answered the MEQ. The domains/factors were formed by(1) questionnaire items related to how people feel in the morning (interpreted as the efficiency of dissipation of sleep pressure or a recovery process); (2) items related to how people feel before sleep (interpreted as the sensitivity to buildup of sleep pressure); and (3) peak time of cognitive arousal. In the following study, these three underlying constructs were confirmed with answers in the MESC using the sample of adolescent. We also tested a bifactor model-S-1 model in the data from the adolescents considering above mentioned factor two as the general factor because sensitivity to the buildup of sleep pressure/phase delay has been proposed tobe themost deterministic aspectsofsleep that drive latter sleep patterns in adolescence. Conclusion: the morningnesseveningness construct found in both scales and ages was found to be multidimensional. By analyzing factors that affect each factor in coming studies it may be possible both to identify people at a higher risk of sleep-related problems and to design factor-specific interventions.